Association between Knowledge, Perceived Seriousness, Perceived Benefit and Barrier, and Family Support on Adherence to Anti-Retrovirus Therapy in Patients with HIV/AIDS - Sunaryo -; Argyo Demartoto; Rita Benya Adriyani (Journal of Health Promotion and Behavior, 2016)
Background: The cumulative of HIV/AIDS cases in Surakarta are 1.212 cases, and 376 of them died in the span of Oktober 2005 until Januari 2014 . HIV infections have not found a cure, so it is possible someone with AIDS often experience psychological problems, especially anxiety, depression, which can suppress the immune system, making people more vulnerable against illness and pain. AIDS can not be cured, but the life expectancy of people living with HIV/ AIDS (PLWHA) can be extended with antiretroviral treatment (ART). This treatment can boost immunity so that the quality of life of PLHIV increasedSubjects and Method: The study was observational analytic research with cross sectional design. The location of research in PHC Manahan Surakarta total of 36 patients with HIV / AIDS who do ARV therapy. The data analysis using logistic regression.Results: There is a positive correlation was not statistically significant from the knowledge of the drugs with antiretroviral therapy adherence (OR=4.03; 95% CI= 0.22 to 73.32; p=0.347). There is a positive correlation was statistically significant on the perception of the seriousness of the disease with antiretroviral therapy adherence (OR=26.70; 95% CI= 1.30 to 550.51; p=0.033). There is a positive relationship and statistically significant on the perception of the benefits and barriers to compliance with antiretroviral therapy (OR=17.73; 95% CI= 1.12 to 279.59; p=0.041). There is a positive correlation was statistically significant from family support with antiretroviral therapy adherence (OR=28.89; 95% CI= 1.24 to 647.71; p=0.036). Conclusion: The perception of the seriousness of the disease is the most variable bergubungan with antiretroviral therapy adherence (p=0.033).Keywords: knowledge about ARV, seriousness of the disease, barriers and family support, adherence ARV therapyCorrespondence: Sunaryo. Department of Health, Surakarta. Email: Sunaryomanahan@gmail.com.Journal of Health Promotion and Behavior (2016), 1(1): 54-61https://doi.org/10.26911/thejhpb.2016.01.01.08